2023
DOI: 10.1021/acsnano.3c09581
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Construction of Degradable DNAzyme-Loaded Nanocapsules for Self-Sufficient Gene Therapy of Pulmonary Metastatic Breast Cancer

Renting Jiang,
Linhu Li,
Ming Li

Abstract: Pulmonary metastasis of breast cancer is the major cause of deaths of breast cancer patients, but the effective treatment of pulmonary metastases is still lacking at present. Herein, a degradable biomimetic DNAzyme biocapsule is developed with the poly­(ethylenimine) (PEI)-DNAzyme complex encapsulated in a Mn2+/Zn2+-coordinated inositol hexaphosphate (IP6) capsule modified with the cRGD targeting peptide for high-efficiency gene therapy of both primary and pulmonary metastatic breast tumors. This DNAzyme bioca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Liu et al (2016) delivered Map3k1-amiRNA into 4T1 breast cancer cells using a miRNA-expressing lentiviral system and showed that MAP3K1 amiRNA attenuated tumor growth and lung metastasis of breast cancer cells in vivo nude mice model. Jiang et al (2023) have constructed DNAzyme nanocapsules, which encapsulate poly -LRB-ethylenimiPEI (PEI)-DNAzyme iMN2 MnZN2/Zn2 +coordinated inositol hexaphosphaIP6(IP6) capsule modified with cRGD targeting peptide, exhibits effective therapeutic efficacy against both primary and metastatic breast tumors inMCF-7CF-7 breast tumor-bearing mouse model. In this study, apoptosis was induced by downregulation of EGR-1 and BCL-2 protein expression.…”
Section: Nanoparticles For Gene Therapy Against Breast Cancer Lung Me...mentioning
confidence: 99%
“…Liu et al (2016) delivered Map3k1-amiRNA into 4T1 breast cancer cells using a miRNA-expressing lentiviral system and showed that MAP3K1 amiRNA attenuated tumor growth and lung metastasis of breast cancer cells in vivo nude mice model. Jiang et al (2023) have constructed DNAzyme nanocapsules, which encapsulate poly -LRB-ethylenimiPEI (PEI)-DNAzyme iMN2 MnZN2/Zn2 +coordinated inositol hexaphosphaIP6(IP6) capsule modified with cRGD targeting peptide, exhibits effective therapeutic efficacy against both primary and metastatic breast tumors inMCF-7CF-7 breast tumor-bearing mouse model. In this study, apoptosis was induced by downregulation of EGR-1 and BCL-2 protein expression.…”
Section: Nanoparticles For Gene Therapy Against Breast Cancer Lung Me...mentioning
confidence: 99%